The role of banking reform policy in transition economies: delayed reforms for the case of Serbia. (5th August 2009) - Bitzenis, Aristidis; Misic, Aleksandra; Marangos, John; Andronikidis, Andreas
While Serbia had initiated the establishment of the two-tier banking system earlier than most of the South East European (SEE) countries (in 1965), the banking reform actually began later than these countries (after 1999). The main reasons to account for that were: 1) very adverse initial conditions of the country's economy; 2) dramatic economic decline; 3) disguised and mixed transition paths that have been followed, imposition of sanctions, severe regional instability, mismanagement and corruption. However, just six years after the implementation of reform, the overall functioning of the banking sector in Serbia in 2005 has witnessed a substantial improvement.